The Role of Public Libraries on Kerman Health Information Seeking Behavior - Maryam Okhovati; Elham Sharifpoor; Mehran Hamzeh Zadeh; Masoomeh Shahsavari; Mahdieh Soltan shahi (مجله انفورماتیک سلامت و زیست پزشکی, 2016)
Introduction: Health clients when seeking health information are faced with challenges such as complexity of the health system, increase in prevalence of chronic diseases, need to participate in the health care, and increase in the available information from different and various sources. Disregarding the importance of health information-seeking behavior and the effectiveness of library services in this field, a few studies have been performed on health information-seeking behavior in developing countries like Iran.